Non-compete covenants, litigation and garden leaves - Azevedo, Alcino (2018)
We develop a dynamic model which assesses non-compete covenants (NCC) and garden leaves (GL) and examine the effect of the uncertainty, embargo period and severance payment on the manager's behavior and the reimbursement amount that is due to the firm if there is a violation of the NCC. We find that if the firm wants to deter the manager from leaving, the NCC is more effective than the GL when the industry uncertainty is low, or the embargo period is long, or the salary of the manager now or when working outside the industry is low, or the salary of the manager when working for the competitor or the gain of the competitor due to the arrival of the manager is high. Otherwise, the GL is more advisable. However, contrary to the usual higher tolerance about GL, our results show that, overall, NCC are less harmful than GL.